Interpretasi Kisah Nabi Musa Perspektif Naratologi al-Qur'ân - M. Faisol (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2017)
The narrative structure of the story of Musa in the Qur'ân is constructed by a plausible and rapid plot. Furthermore, this story has a constant narrative structure that is narrator-creator-sender (Allah) as the one who sends the message, the first receiver (the Prophet Muhammad) as the messenger of God's message to be transmitted to mankind, and the second receiver is all mankind. Other than that, the narrative structure of the story of Musa in the Qur'ân has an ethical function. It brings spiritual-eschatological vision to mankind. Through interpersonal relation structure and the representation concept of time and place, the story of Musa gives theological and moral values. The one that distinguishes the narrative function of the story of Musa in the Qur'ân from the other stories created by people is the rhetoric clarity (al-bu'd al-bayānī). The Qur'ân always uses simple and meaningful rhetoric. Thus, in presenting the story of Musa, the Qur'ân only exposes important events that conform to religious purposes (al-ghard al-dīnī).